Introduction of Poems in the Poems of rare and novelist: An analytical Study - Ibraheem, Ali Dhedan (Al-Adab Journal, 2020)
The Poetic Introduction, translate the artists skill in the face for the Purpose of the Poem, the Poets Portrayed in their editorials various Paintings, including the tablet of the drums and the dice and the Wisdom, describing the graying and the Weeping of the youth as well as describing the Position of the blames and Introductions that carried religious.